2018
DOI: 10.1007/s00213-018-4829-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine self-administration on incentive salience in male Sprague Dawley rats

Abstract: The results suggest that nicotinic enhancement of incentive salience is transient, and a previous history of nicotine use does not cause further sensitization. Taken together, these results suggest that nicotine enhances incentive salience, particularly-and perhaps exclusively-while onboard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…In rats trained with the same nicotine dose and schedule, we previously reported that substituting saline for nicotine before a Pavlovian conditioning session resulted in a reduction in behavior that returned the nicotine-enhanced CRs to the level of control animals [22]. Furthermore, at blood plasma levels relevant to human cigarette inhalation, self-administered nicotine increases sign-tracking behaviors, but this effect may be transient and dissipate when nicotine is no longer on board, despite an extensive history of drug exposure [24]. Thus, it is possible that despite 30 days of nicotine exposure, the nicotine dose in this study was not sufficient to elicit changes in BDNF expression measurable after 24 h.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats trained with the same nicotine dose and schedule, we previously reported that substituting saline for nicotine before a Pavlovian conditioning session resulted in a reduction in behavior that returned the nicotine-enhanced CRs to the level of control animals [22]. Furthermore, at blood plasma levels relevant to human cigarette inhalation, self-administered nicotine increases sign-tracking behaviors, but this effect may be transient and dissipate when nicotine is no longer on board, despite an extensive history of drug exposure [24]. Thus, it is possible that despite 30 days of nicotine exposure, the nicotine dose in this study was not sufficient to elicit changes in BDNF expression measurable after 24 h.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine, in particular, exerts reinforcement- and incentive-enhancing properties in both humans and animals, suggesting that nicotine amplifies the rewarding or incentive properties of non-nicotine stimuli [17–20]. For example, nicotine increases CRs to a non-drug-associated CS [18, 21, 22], especially sign-tracking CRs [16, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that stimuli associated with food (test chamber, house-light, lever insertion) mediated the nicotinic effects on motivation. Nicotine enhances the incentive value of such stimuli, facilitating a conditioned approach to them ( sign tracking , Palmatier et al, 2013; Overby et al, under review). In the presence of the lever press-food contingency, it is likely that such approach would be directed to the lever.…”
Section: Discussionmentioning
confidence: 99%
“…Albans, VT), which have been previously described in detail (Overby, Daniels et al 2018, Leyrer-Jackson, Overby et al 2020.…”
Section: Food Training Proceduresmentioning
confidence: 99%